Копытные позднего неогена юга Ервопейской части СССР - Короткевич, Е.Л. (Вестник зоологии, 1977)
Definite landscape-climatic changes that had taken place in the South of the USSR European section in Late Neogene are outlined on the basis of reviewing Ungulata of the hipparion fauna in the South of the Ukrainian SSR. These changes were pronounced in a gradual decrease of the river humid biotopes and spread at first of semi-opened forest-steppe-savanna landscapes and then more dry open, steppe and somewhere even semi-desert ones. Besides, for the studied period of time a definite cyclicity, alternation of more dry and humid periods, is marked.